Du camp à l’asile : Les hospitalisations psychiatriques d’internés et de détenus politiques pendant la guerre d’indépendance algérienne - Paul Marquis (L’Année du Maghreb)
Throughout the Algerian War of independence, dozens of political detainees were subjected to psychiatric hospitalization after being jailed or interned. By looking at conditions for hospitalizing individuals brought from camps and prisons, this article seeks to highlight how the psychiatric institution deals with the requirements and practices of prison and internment camps between 1954 and 1962. A study of case files from hospitalized prisoners tends to show that the therapeutic perspectives of psychiatrists were systematically subordinated to the repressive logic of the penal administration.